Willingness to Pay for Restoring a Degraded Freshwater Lake Ecosystem: The Case of Lake Bosomtwe, Ghana (International Journal of Sustainable Rural Development, 2024)
Lake Bosomtwe, a UNESCO biosphere reserve is a vital source of livelihood for the surrounding communities. They rely on fish catches for cash and protein. The lake’s ecosystem services (ESs) value have declined due to human activities. Managing the Lake’s ESs is hindered by the community’s insufficient engagement and participation in conservation efforts. The surrounding communities Willingness to Pay for the cost of restoration efforts are currently unknown. Therefore, this study assessed the community peoples’ Willingness to Pay for restoration of degraded natural freshwater Lake Bosomtwe ecosystem. Using convenience sampling, 150 respondents from 15 communities surrounding the Lake was selected and interviewed through a semi structured questionnaire. Contingent Valuation Method was used to determine respondents’ Willingness to Pay and multiple regression was used to identify factors that affected respondents’ Willingness to Pay towards a restoration project. The results showed that majority of the respondents are aware of the ESs provided by the ecosystem of Lake Bosomtwe. Also, the results showed that, majority of the respondents’ activities within the Lakes’ environs are unfavorable towards the sustainability of the ESs. Lack of employment is among the factors hindering respondents’ Willingness to Pay. The average Willingness to Pay amount is twenty Ghana cedi and fifty-five pesewas (GHȼ20.55) per person monthly. About 78.67% respondents’ Willingness to Pay results shows willingness to engage in a restoration program to protect Lake Bosomtwe. Key stakeholders involved in the protection of the Lake should provide alternative livelihood and social amenities to control the Lake’s ecosystem degradation as recommended.